2015
DOI: 10.1371/journal.pone.0120293
|View full text |Cite
|
Sign up to set email alerts
|

The White Collar Complex Is Involved in Sexual Development of Fusarium graminearum

Abstract: Sexual spores (ascospores) of Fusarium graminearum, a homothallic ascomycetous fungus, are believed to be the primary inocula for epidemics of the diseases caused by this species in cereal crops. Based on the light requirement for the formation of fruiting bodies (perithecia) of F. graminearum under laboratory conditions, we explored whether photoreceptors play an important role in sexual development. Here, we evaluated the roles of three genes encoding putative photoreceptors [a phytochrome gene (FgFph) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
(74 reference statements)
0
23
1
Order By: Relevance
“…Light sensing relays several important processes of fruiting body development, including its initiation, stimulating growth in the right direction and sensing seasonal light/dark periodicity that triggers fruiting (Pöggeler et al ., ; Kamada et al ., ). Many of these responses are mediated by the blue light receptor white collar complex (WCC) which, including its regulatory role in fruiting body development, is conserved widely (Idnurm & Heitman, ; Rodriguez‐Romero et al ., ; Verma & Idnurm, ), although the specific interaction may differ even among closely related species (Purschwitz et al ., ; Kim et al ., ). The WCC regulates sexual reproduction through mating genes (Idnurm & Heitman, ) in all fungal species examined so far (Idnurm & Heitman, ), except for budding and fission yeasts in which the WCC has been lost (Nguyen et al ., ).…”
Section: How Many Origins Of Complex Multicellularity In Fungi?mentioning
confidence: 97%
“…Light sensing relays several important processes of fruiting body development, including its initiation, stimulating growth in the right direction and sensing seasonal light/dark periodicity that triggers fruiting (Pöggeler et al ., ; Kamada et al ., ). Many of these responses are mediated by the blue light receptor white collar complex (WCC) which, including its regulatory role in fruiting body development, is conserved widely (Idnurm & Heitman, ; Rodriguez‐Romero et al ., ; Verma & Idnurm, ), although the specific interaction may differ even among closely related species (Purschwitz et al ., ; Kim et al ., ). The WCC regulates sexual reproduction through mating genes (Idnurm & Heitman, ) in all fungal species examined so far (Idnurm & Heitman, ), except for budding and fission yeasts in which the WCC has been lost (Nguyen et al ., ).…”
Section: How Many Origins Of Complex Multicellularity In Fungi?mentioning
confidence: 97%
“…BLR1 and BLR2 only play minor roles in the transcriptional regulation of the pheromone response pathway and sexual development (Seibel et al ., ), although important functions were shown for their homologues in the homothallic Fusarium graminearum (Kim et al ., ). In contrast, deletion of env1 leads to strong upregulation of both pheromone precursor and pheromone receptor genes, and causes female sterility (Seibel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…As found in the F. graminearum strain Z-3639, WCC should be required for the normal maturity of perithecia during sexual development [40]. However, another group later reported that WCC could negatively regulate sexual development in another strain of F. graminearum; the Z-3643 [30]. In the present study, the perithecial maturation and ascospore formation of F. asiaticum are dependent on the presence of the WCC.…”
Section: Discussionmentioning
confidence: 42%
“…Sexual reproduction is usually vital for the dissemination of fungal pathogens in their lifecycles, and the near-UV light is known to induce the perithecia maturation and ascospore formation in FGSC [39]. However, two independent studies reported inconsistent effects of the WCC photoreceptor on the sexual development of F. graminearum, which was probably due to the difference of the wild-type background strains used in each study [30,40]. The present work with F. asiaticum showed that the WT strain was able to form mature perithecia, in which the sexual ascospores could be found apparently.…”
Section: Perithecia Maturation and Ascospore Development Of F Asiatimentioning
confidence: 99%